Synthesis of Cobalt Phosphide Nanoparticles Supported on Pristine Graphene by Dynamically Self-Assembled Graphene Quantum Dots for Hydrogen Evolution - Wang, Xiaoyan (2017)
A highly active, durable, and low-cost hydrogen evolution reaction (HER) catalyst is desirable for energy storage through water splitting but its fabrication presents great challenges. Herein, mediated by dynamically self-assembled graphene quantum dots (GQDs), small, uniform, high-density, and well-dispersed CoP nanoparticles were grown in situ on pristine graphene for the first time. This hybrid nanostructure was then employed as HER electrocatalyst, showing an onset potential of 7 mV, an overpotential of 91.3 mV to achieve 10 mA cm−2, a Tafel slope of 42.6 mV dec−1, and an exchange current density of 0.1225 mA cm−2, all of which compare favorably to those of most reported non-noble-metal catalysts. The developed catalyst also exhibits excellent durability with negligible current loss after 2000 cyclic voltammetry cycles (+0.01 to −0.17 V vs. RHE) or 34 h of chronoamperometric measurement at an overpotential of 91.3 mV. This work not only develops a new strategy for the fabrication of high-performance and inexpensive electrocatalysts for HER but also provides scientific insight into the mechanism of the dynamically self-assembled GQDsmediated synthesis process.